Resin composition for foam molding, foam molded body, and method for producing foam molded body
Patent Information
- Application Number
- CN202580017386.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-28
- Filing Date
- 2025-03-04
- Publication Date
- 2026-09-22
AI Technical Summary
[0032]根据本公开,能够提供即使不是特殊的氟树脂也能够形成良好的气泡的发泡成型用树脂组合物、发泡成型体和发泡成型体的制造方法。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This disclosure relates to resin compositions for foam molding, foamed articles, and methods for manufacturing foamed articles. Background Technology
[0002] Fluoropolymers are widely used in various applications due to their excellent heat resistance and chemical resistance.
[0003] Foaming molding is a known method for achieving lightweighting and improved electrical properties of fluoropolymers. For example, Patent Document 1 describes the formation of good bubbles by melt foaming molding a specific thermoplastic fluoropolymer material.
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: Japanese Patent Application Publication No. 2015-004057 Summary of the Invention
[0007] The problem that the invention aims to solve
[0008] However, there is room for improvement in the method of Patent Document 1 regarding the limitation on the type of fluororesin.
[0009] The purpose of this disclosure is to provide a resin composition for foaming molding, a foamed body, and a method for manufacturing a foamed body that can form good bubbles even if it is not a special fluoropolymer.
[0010] Methods for solving problems
[0011] This disclosure (1) is a resin composition for foaming molding, comprising a fluororesin (A) and a compound (B), wherein the crystallite size of the compound (B) is greater than 100 Å in X-ray diffraction and the volatile content at 330°C is less than 7.0% by mass, and the compound (B) is dispersed in the fluororesin (A) with a center-to-gravity distance of less than 5.0 μm.
[0012] This disclosure (2) is a resin composition for foaming as described in this disclosure (1), wherein the fluororesin (A) is a fluororesin capable of melt molding.
[0013] This disclosure (3) is a resin composition for foaming molding as described in disclosure (1) or (2), wherein the fluororesin (A) is at least one selected from the group consisting of tetrafluoroethylene / hexafluoropropylene copolymers and tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymers.
[0014] This disclosure (4) is a foaming resin composition as described in any one of (1) to (3) of this disclosure, wherein the fluororesin (A) is a tetrafluoroethylene / hexafluoropropylene copolymer.
[0015] This disclosure (5) is a foaming resin composition as described in any one of disclosures (1) to (4), wherein the fluororesin (A) is fluorinated.
[0016] This disclosure (6) is a foaming resin composition as described in any one of disclosures (1) to (5), wherein the content of the fluororesin (A) is 80 to 99.99% by mass.
[0017] This disclosure (7) is a foaming resin composition as described in any one of disclosures (1) to (6), wherein the content of the fluororesin (A) is 97% by mass or more and less than 99.85% by mass.
[0018] The resin composition for foaming molding as described in any one of (1) to (7) of this disclosure (8) is substantially free of fluorine-based low molecular weight compounds.
[0019] This disclosure (9) is a foaming resin composition as described in any one of disclosures (1) to (8), wherein the crystallite size of the compound (B) in X-ray diffraction is 200 to 1000 Å and the volatile content at 330°C is less than 1.0% by mass.
[0020] This disclosure (10) is a foaming resin composition as described in any one of disclosures (1) to (9), wherein the compound (B) is dispersed in the fluororesin (A) with a center-to-gravity distance of 0.5 to 2.0 μm.
[0021] This disclosure (11) is a foaming resin composition as described in any one of disclosures (1) to (10), wherein the compound (B) has a density of 15,000 particles / mm². 2 The above are dispersed in the fluororesin (A).
[0022] This disclosure (12) is a foaming resin composition as described in any one of disclosures (1) to (11), wherein the compound (B) is dispersed in the fluororesin (A) with a particle size of less than 4.0 μm.
[0023] This disclosure (13) is a foaming resin composition as described in any one of disclosures (1) to (12), wherein the thermal decomposition temperature of said compound (B) is 270°C or higher.
[0024] This disclosure (14) is a resin composition for foaming molding as described in any one of disclosures (1) to (13), wherein the compound (B) comprises at least one selected from the group consisting of tetrapyrrole cyclic compounds, barium sulfate, silica and alumina.
[0025] This disclosure (15) is a foaming resin composition as described in any one of disclosures (1) to (14), wherein the compound (B) comprises copper phthalocyanine.
[0026] This disclosure (16) is a foaming molding resin composition as described in any one of disclosures (1) to (15), wherein the content of compound (B) is 0.1 to 20 parts by weight relative to 100 parts by weight of the fluororesin (A).
[0027] This disclosure (17) is a foaming molding resin composition as described in any one of disclosures (1) to (16), wherein the content of compound (B) is 0.5 to 2.0 parts by weight relative to 100 parts by weight of the fluororesin (A).
[0028] This disclosure (18) is a foamed molded body formed using any one of the foamed molding resin compositions described in any one of disclosures (1) to (17).
[0029] This disclosure (19) is a method for manufacturing a foamed molded article, which includes a step of foaming and molding the resin composition for foaming and molding as described in any one of the disclosures (1) to (17).
[0030] This disclosure (20) is a method for manufacturing a foamed molded article as described in this disclosure (19), wherein the foaming is intermittent foaming.
[0031] Invention Effects
[0032] According to this disclosure, a resin composition for foaming molding, a foamed molded body, and a method for manufacturing a foamed molded body are provided that can form good bubbles even if they are not special fluoropolymers. Detailed Implementation
[0033] The following details this disclosure.
[0034] The foaming molding resin composition disclosed herein comprises a fluoropolymer (A) and a compound (B), wherein the crystallite size of the compound (B) is greater than 100 Å by X-ray diffraction and the volatile content at 330°C is less than 7.0% by mass, and the compound (B) is dispersed in the fluoropolymer (A) with a center-to-gravity distance of less than 5.0 μm.
[0035] In the resin composition for foaming molding disclosed herein, compound (B) satisfying the above conditions functions as a foaming nucleating agent. By having a crystallite size greater than 100 Å and a centroid distance of 5.0 μm or less, the bubble size in the foamed molded body becomes smaller, thereby increasing the number of bubbles generated. Furthermore, by having a volatilization rate of 7.0% by mass or less at 330°C, bubble coalescence can be suppressed.
[0036] Fluoropolymer (A) can be any fluorinated resin, but is preferably a melt-processable fluorine resin. Examples of melt-processable fluorine resins include tetrafluoroethylene (TFE) / hexafluoropropylene (HFP) copolymers [FEP], TFE / perfluoro(alkyl vinyl ether) (PAVE) copolymers [PFA], TFE / ethylene copolymers [ETFE], trifluorochloroethylene (CTFE) / ethylene copolymers [ECTFE], polyvinylidene fluoride [PVdF], polychlorotrifluoroethylene [PCTFE], TFE / vinylidene fluoride (VdF) copolymers [VT], polyvinyl fluoride [PVF], TFE / VdF / CTFE copolymers [VTC], TFE / ethylene / HFP copolymers, and TFE / HFP / VdF copolymers. One or more of these can be used.
[0037] Examples of PAVEs mentioned above include perfluoro(methyl vinyl ether) [PMVE], perfluoro(ethyl vinyl ether) [PEVE], and perfluoro(propyl vinyl ether) [PPVE]. Among these, PPVE is preferred. One or more of these can be used.
[0038] Fluoropolymer (A) may contain polymerization units based on other monomers in an amount that does not impair the essential properties of each fluoropolymer. Other monomers may be appropriately selected from, for example, TFE, HFP, ethylene, propylene, perfluoro(alkyl vinyl ether), perfluoroalkyl ethylene, hydrofluoroolefin, fluoroalkyl ethylene, perfluoro(alkyl allyl ether), etc. One or more of these may be used. As the perfluoroalkyl group constituting the other monomer, a perfluoroalkyl group having 1 to 10 carbon atoms is preferred.
[0039] Other monomers can be monomers with polar groups. Examples of monomers with polar groups include hydroxyl alkyl vinyl ethers such as hydroxyethyl vinyl ether, hydroxypropyl vinyl ether, hydroxybutyl vinyl ether, hydroxyisobutyl vinyl ether, and hydroxycyclohexyl vinyl ether (all non-fluorinated monomers with hydroxyl groups); acrylic acid, methacrylic acid, itaconic acid, succinic acid, fumaric acid, crotonic acid, maleic acid, citraconic acid, undecenoic acid, and ethynyl dicarboxylic acid (all non-fluorinated monomers with carboxyl groups); itaconic anhydride (hereinafter also denoted as "IAH"), citraconic anhydride (hereinafter also denoted as "CAH"), and 5-norbornene. Non-fluorinated monomers with anhydride residues, such as 2,3-dicarboxylic anhydride (hereinafter also referred to as "NAH"), succinic anhydride, fumaric anhydride, and maleic anhydride; non-fluorinated monomers with sulfonic groups, such as vinyl sulfonic acid; non-fluorinated monomers with epoxy groups (glycidyl groups), such as glycidyl vinyl ether and glycidyl allyl ether; non-fluorinated monomers with amino groups, such as aminoalkyl vinyl ether and aminoalkyl allyl ether; non-fluorinated monomers with amide groups, such as (meth)acrylamide and hydroxymethylacrylamide; and non-fluorinated monomers with nitrile groups, such as acrylonitrile and methacrylonitrile.
[0040] From the perspective of excellent heat resistance, the fluoropolymer (A) is preferably at least one selected from the group consisting of TFE / HFP copolymers and TFE / PAVE copolymers, and more preferably a TFE / HFP copolymer. Furthermore, from the perspective of superior electrical properties, a perfluorinated resin is also preferred.
[0041] The TFE / HFP ratio of the TFE / HFP copolymer is preferably 80-97 / 3-20 by mass, and more preferably 84-92 / 8-16.
[0042] TFE / HFP copolymers can be binary copolymers composed of TFE and HFP, or terpolymers composed of TFE, HFP and comonomers that can copolymerize with TFE and HFP (e.g., TFE / HFP / PAVE copolymers).
[0043] TFE / HFP copolymers are also preferably TFE / HFP / PAVE copolymers containing PAVE-based polymerization units.
[0044] The TFE / HFP / PAVE copolymer preferably has a mass ratio of 70–97 / 3–20 / 0.1–10, more preferably 81–92 / 5–16 / 0.3–5.
[0045] The TFE / PAVE ratio of the TFE / PAVE copolymer is preferably 90-99 / 1-10 by mass, and more preferably 92-97 / 3-8.
[0046] The TFE / ethylene molar ratio of the TFE / ethylene copolymer is preferably 20–80 / 20–80, more preferably 40–65 / 35–60. Furthermore, the TFE / ethylene copolymer may contain other monomer components.
[0047] That is, TFE / ethylene copolymers can be binary copolymers composed of TFE and ethylene, or terpolymers composed of TFE, ethylene and comonomers that can copolymerize with TFE and ethylene (e.g., TFE / ethylene / HFP copolymers).
[0048] TFE / ethylene copolymers are also preferably TFE / ethylene / HFP copolymers containing HFP-based polymerization units. The molar ratio of TFE / ethylene / HFP in the TFE / ethylene / HFP copolymer is preferably 40-65 / 30-60 / 0.5-20, more preferably 40-65 / 30-60 / 0.5-10.
[0049] In this specification, the melt flow rate (MFR) for melt molding is preferably 1 to 100 g / 10 min. The MFR of the fluoropolymer (A) is more preferably 5 to 70 g / 10 min, further preferably 10 to 60 g / 10 min, and even more preferably 15 to 50 g / 10 min, even more preferably 20 to 45 g / 10 min, and particularly preferably 30 to 45 g / 10 min, from the perspective of suppressing spark generation and increasing foaming rate.
[0050] The above MFR is a value measured according to ASTM D-1238, using a die with a diameter of 2.1 mm and a length of 8 mm, at 372°C and a load of 5 kg.
[0051] Fluororubber (A) may contain non-meltable fluoropolymers along with meltable fluoropolymers. When fluoropolymer (A) contains non-meltable fluoropolymers, their content relative to the total amount of fluoropolymer (A) is preferably 0.001 to 3.0% by mass.
[0052] It should be noted that, in this specification, "unable to melt-form" means that the above-mentioned MFR is less than 1 g / 10 minutes. The above-mentioned MFR is preferably less than 0.1 g / 10 minutes.
[0053] Examples of non-melt-formable fluoropolymers include polytetrafluoroethylene (PTFE). Other examples of melt-formable fluoropolymers include FEP, PFA, ETFE, PCTFE, and PVDF. One or more of these can be used. PTFE is preferred.
[0054] It should be noted that FEP and other fluoropolymers are non-melt-forming when the MFR is less than 1 g / 10 min, and are melt-forming when the MFR is greater than 1 g / 10 min.
[0055] In this disclosure, PTFE can be a tetrafluoroethylene [TFE] homopolymer or a modified polytetrafluoroethylene [modified PTFE] obtained from TFE and trace amounts of comonomers.
[0056] TFE homopolymers are obtained by polymerizing only tetrafluoroethylene [TFE] as a monomer. As trace comonomers in modified PTFE, there are no particular limitations on any fluorinated compound that can copolymerize with TFE; examples include perfluoroolefins such as hexafluoropropylene [HFP]; various perfluorovinyl ethers [PFVE] such as PAVE; fluorinated m-dioxane; trifluoroethylene; and vinylidene fluoride.
[0057] In modified PTFE, the content of trace monomer units from the above-mentioned trace monomers in all monomer units is typically in the range of 0.001 to 1.0% by mass.
[0058] In this specification, "the content (mass%) of trace monomer units in all monomer units" refers to the mass fraction (mass%) of the trace monomers from which the aforementioned trace monomer units originate in the total amount of monomers from which "all monomer units" originate, i.e., the total amount of monomers constituting the fluoropolymer.
[0059] From the perspective of heat resistance and electrical properties, the standard specific gravity [SSG] of PTFE is preferably 2.15 to 2.30, more preferably 2.25 or less, and even more preferably 2.22 or less.
[0060] High molecular weight PTFE with an SSG of less than 2.15 does not exclude the effects of this disclosure, but it is difficult and impractical to manufacture.
[0061] SSG is a value determined according to ASTM D4895-89, based on the water displacement method.
[0062] When PTFE has a low SSG (Self-Strain Gain), a small amount can increase its biaxial tensile viscosity. When the SSG is high, increasing the amount added will produce the same effect.
[0063] PTFE can be prepared by known methods such as emulsion polymerization and suspension polymerization. Emulsion polymerization is preferred as the polymerization method.
[0064] When PTFE aggregates are present in the foaming resin composition disclosed herein, frequent sparking may occur during wire coating molding, leading to a deterioration in the defect rate. Therefore, the average primary particle size of PTFE is preferably 50 to 800 nm, more preferably 50 to 500 nm.
[0065] The average primary particle size of PTFE is determined as follows: For a polymer latex diluted with water to a solid content of 0.22% by mass, the transmittance of transmitted light at a wavelength of 500 nm per unit length is measured. The average primary particle size of PTFE is obtained by pre-measuring the directional diameter in a transmission electron microscope image. The average primary particle size of PTFE is determined based on a standard curve of the average primary particle size of PTFE and the aforementioned transmittance.
[0066] Fluoropolymer (A) can be synthesized by polymerizing monomer components using common polymerization methods, such as emulsion polymerization, suspension polymerization, solution polymerization, bulk polymerization, and gas-phase polymerization. Chain transfer agents such as methanol are sometimes used in these polymerization reactions. Fluoropolymer (A) can also be manufactured through polymerization and separation without the use of reagents containing metal ions.
[0067] Fluoropolymer (A) is not particularly limited and may have terminal groups such as -CF3 or -CF2H at at least one site of the polymer backbone and polymer side chain, preferably having a -CF3 terminal group. Fluoropolymers having these terminal groups are obtained by fluorination treatment.
[0068] Unfluorinated fluororesins sometimes possess end groups with unstable thermal and electrical properties, such as -COOH, -CH2OH, -COF, and -CONH2 (hereinafter, such end groups will also be referred to as "unstable end groups"). These unstable end groups can be reduced through the aforementioned fluorination treatment. Fluorinated resin (A) preferably contains few or no of the aforementioned unstable end groups, and more preferably, the total number of the above four unstable end groups and the -CF2H end group is less than 1×10⁻⁶. 6 The number of carbon atoms is 50 or less. If it exceeds 50, poor molding may occur. More preferably, the number of unstable terminal groups is 20 or less, and even more preferably 10 or less.
[0069] In this specification, the number of unstable terminal groups mentioned above is a value obtained from infrared absorption spectroscopy. The aforementioned unstable terminal groups and -CF2H terminal groups may be absent, and all may be -CF3 terminal groups.
[0070] Fluorination can be performed by contacting an unfluorinated fluoropolymer with a fluorinated compound.
[0071] There are no particular limitations on fluorine-containing compounds; any fluorine radical source that generates fluorine radicals under fluorination conditions can be cited. Examples of fluorine radical sources include F2 gas, CoF3, AgF2, UF6, OF2, N2F2, CF3OF, and fluorinated halogens (e.g., IF5, ClF3). One or more of these can be used.
[0072] Fluorine radical sources such as F2 gas can be 100% concentrated, preferably diluted to 5-50% by mass, more preferably to 15-30% by mass, after mixing with an inert gas. Examples of inert gases include nitrogen, helium, and argon; from an economic perspective, nitrogen is preferred.
[0073] The conditions for fluorination are not particularly limited. Molten fluoropolymer can be brought into contact with a fluorinated compound. Fluorination is typically carried out at a temperature below the melting point of the fluoropolymer, preferably 20–220°C, and more preferably 100–200°C. Fluorination usually lasts for 1–30 hours, preferably 5–20 hours.
[0074] Fluorination treatment preferably involves contacting the unfluorinated fluoropolymer with fluorine gas (F2 gas).
[0075] As for the fluoropolymer (A), there are no particular limitations. From the perspective of obtaining a foamed molded article with excellent heat resistance and a wide continuous operating temperature range, a melting point of 200°C or higher, a molding temperature of 250°C or higher, and a thermal decomposition temperature of 300°C or higher are preferred. Furthermore, a melting point of 250°C or higher is more preferred, and 320°C or lower is more preferably preferred. A molding temperature of 300°C or higher is more preferably preferred, and 450°C or lower is more preferably preferred. A thermal decomposition temperature of 350°C or higher is more preferably preferred, and 400°C or higher is even more preferably preferred. The upper limit for the melting point, molding temperature, and thermal decomposition temperature is 600°C or lower.
[0076] In this specification, the melting point is the temperature determined by differential scanning calorimetry (DSC), the molding temperature is the generally recommended temperature suitable for molding, and the temperature at which the resin exhibits fluidity without causing coloration or other resin degradation. The thermal decomposition temperature is the 1% weight loss temperature when heated in air at 10°C / min using TG (thermal weight change measurement). However, the weight loss due to the volatilization of water or water of crystallization observed between 100°C and 200°C is not included. Fluidity is defined as an MFR of 0.0001 or higher at this temperature.
[0077] To reduce signal loss in communication cables, the dielectric constant of the fluoropolymer (A) is preferably 3.0 or less, more preferably 2.5 or less, even more preferably 2.3 or less, and most preferably 2.1 or less. A lower limit of 1.0 or more is preferred. Similarly, the dielectric loss tangent is preferably 0.01 or less, more preferably 0.002 or less, even more preferably 0.001 or less, and most preferably 0.0005 or less. A lower limit of 0.0001 or more is preferred. The dielectric constant and dielectric loss tangent are determined using a cavity resonator method at a frequency of 6 GHz.
[0078] The content of fluoropolymer (A) is preferably 80% by mass or more, more preferably 90% by mass or more. Further preferably 95% by mass or more, particularly preferably 97% by mass or more. As an upper limit, it is preferably 99.99% by mass or less, more preferably 99.85% by mass or less, and even more preferably less than 99.85% by mass.
[0079] The foaming resin composition disclosed herein may contain a resin different from the fluoropolymer (A). Examples of resins different from the fluoropolymer (A) include general-purpose resins such as polyethylene resin, polypropylene resin, vinyl chloride resin, and polystyrene resin; and engineering plastics such as nylon, polycarbonate, polyetheretherketone resin, polyphenylene sulfide resin, polyaryletherketone (PAEK), polyetherketoneketone (PEKK), polyetherketone (PEK), polyetheretherketoneketone (PEEKK), polyethersulfone (PES), liquid crystal polymer (LCP), polysulfone (PSF), amorphous polyarylene ester (PAR), polyether nitrile (PEN), thermoplastic polyimide (TPI), polyimide (PI), polyetherimide (PEI), and polyamide-imide (PAI). One or more of these resins may be used.
[0080] The content of the resin different from fluoropolymer (A) is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 1% by mass or less. The lower limit is not particularly limited and can be 0% by mass.
[0081] The resin composition for foaming molding disclosed herein contains compound (B) as a foaming nucleating agent.
[0082] Compound (B) only requires a crystallite size greater than 100 Å in X-ray diffraction (XRD), preferably greater than 140 Å, and more preferably greater than 200 Å. This allows for the formation of an ideal lattice with low strain, promoting bubble formation. The upper limit of the crystallite size is preferably 10,000 Å or less, more preferably 5,000 Å or less, and even more preferably 1,000 Å or less.
[0083] XRD was performed using an X-ray diffraction apparatus: Smart Lab, manufactured by Rigaku Corporation, and the powder was measured using SmartLab StudioII software. The X-ray source was CuKα with a wavelength of 1.54 Å, and the diffraction angle (2θ) was set to 5°–90°. The crystallite size was calculated using the Scherrer formula based on the maximum half-width of the obtained diffraction peaks.
[0084] D=K×λ / (β×cosθ)…Scherrer’s formula
[0085] D: Crystalline size (Å)
[0086] K: Scherrer constant
[0087] λ: X-ray wavelength (Å)
[0088] β: Half-width of the diffraction peak (rad)
[0089] θ: 1 / 2 (rad) of the diffraction angle
[0090] Scherrer constant (K) = 0.94, X-ray wavelength (λ) = 1.5418. The case where the obtained diffraction spectrum does not contain diffraction peaks originating from a crystal structure is considered as the case where there is no crystal structure.
[0091] Compound (B) only needs to have a volatility of 7.0% by mass or less at 330°C, preferably 5.0% by mass or less, more preferably 3.0% by mass or less, and particularly preferably 1.0% by mass or less. This suppresses the formation of residues (accumulations) that can cause molding defects, enabling long-term molding processes such as wire molding. The lower limit is not particularly limited and can be 0% by mass.
[0092] Regarding the amount of volatilization, the reduction in mass of the sample when it is kept at 330°C for 1 hour in an electric furnace is measured and calculated as the reduction in mass / the mass before holding the sample × 100.
[0093] Compound (B) can be dispersed in fluororesin (A) with a center-to-center distance of less than 5.0 μm. The upper limit of the center-to-center distance is preferably less than 3.0 μm, more preferably less than 2.0 μm, and the lower limit is preferably more than 0.01 μm, more preferably more than 0.1 μm, and even more preferably more than 0.5 μm.
[0094] From the perspective of forming more uniform bubbles, compound (B) is preferably prepared at a density of 15,000 bubbles / mm². 2 The above are dispersed in fluororesin (A). A more preferred lower limit for density is 30,000 particles / mm². 2 The above is further optimized to 120,000 pieces / mm. 2The upper limit is preferably 10,000,000 pieces / mm. 2 The following is preferred: 5,000,000 pieces / mm 2 The following is a further preferred value: 1,000,000 pieces / mm 2 the following.
[0095] From the perspective of forming more uniform bubbles, compound (B) is preferably dispersed in fluororesin (A) with a particle size of 4.0 μm or less. The upper limit of the particle size is more preferably 3.0 μm or less, further preferably 2.0 μm or less, and the lower limit is preferably 0.001 μm or more, more preferably 0.01 μm or more, and further preferably 0.1 μm or more.
[0096] The dispersion state (intercenter-to-center distance, density, and particle size) of compound (B) in fluoropolymer (A) was calculated by image processing of a cross-section of the resin composition containing fluoropolymer (A) and compound (B) taken at 150x magnification using a laser microscope (KEYENCE VK-X1000 shape analysis laser microscope). The intercenter-to-center distance and particle size are averages of 100 particles.
[0097] As for compound (B), there are no particular limitations as long as the above conditions are met, and it may include tetrapyrrole cyclic compounds, barium sulfate, silicon dioxide, aluminum oxide, etc. They may be used alone or in combination of two or more. Preferably, it includes at least one of the following: tetrapyrrole cyclic compounds, barium sulfate, silicon dioxide, and aluminum oxide; more preferably, it includes tetrapyrrole cyclic compounds.
[0098] However, the type of component is not important; what matters is meeting the above conditions. Even with the same components, different crystallization states, dispersion states, and volatilization rates will not yield the same results. For crystallization state, it is important that the crystallite size in X-ray diffraction (XRD) is greater than 100 Å. For dispersion state, it is important that the distance between the centers of gravity is less than 5.0 μm in the fluoropolymer (A). For volatilization rate, it is important that the volatilization rate at 330°C is less than 7.0% by mass.
[0099] Tetrapyrrole cyclic compounds are classified into three types based on their skeletons: phthalocyanine, dihydroporphyrin, and chlorophyll. Additionally, they can form complexes with metals, such as copper, iron, and magnesium.
[0100] From the perspective of its good function as a foaming nucleating agent, as a tetrapyrrole cyclic compound, a compound having a phthalocyanine skeleton is preferred, a metal phthalocyanine is more preferred, and a copper phthalocyanine is even more preferred.
[0101] Compound (B) preferably does not decompose, dissolve in the fluoropolymer (A), or melt at the molding temperature during foaming. That is, when the foaming resin composition of this disclosure is foamed, compound (B) is preferably a solid in the composition. This allows it to fully function as a foaming nucleating agent.
[0102] The fact that compound (B) meets this condition can be confirmed by observing whether compound (B) exists in a solid state when heated to a specified temperature using a polarizing microscope equipped with a heated stage.
[0103] The melting temperature (melting point) of compound (B) is preferably 300°C or higher, more preferably 320°C or higher, and even more preferably 350°C or higher. Within this range, it does not easily melt even at the molding temperature during foaming, thus fully realizing its function as a foaming nucleating agent. There is no particular upper limit, but it is preferably 1000°C or lower.
[0104] The thermal decomposition temperature of compound (B) is preferably 270°C or higher, more preferably 320°C or higher, and even more preferably 350°C or higher. Within this range, it is less prone to decomposition even at the molding temperature during foaming. Therefore, adverse effects caused by the decomposition of compound (B) (e.g., reduced electrical properties, bubble rupture, and coating breakage during wire molding) can be suppressed. The upper limit is not particularly limited, but is preferably 1000°C or lower.
[0105] The melting temperature (melting point) and thermal decomposition temperature of compound (B) can be determined using the same method as those used for the fluoropolymer (A) described above.
[0106] In the resin composition for foaming molding disclosed herein, the content of compound (B) relative to 100 parts by weight of fluororesin (A) is preferably 0.1 parts by weight or more, more preferably 0.3 parts by weight or more, even more preferably 0.5 parts by weight or more, and preferably 20 parts by weight or less, more preferably 5.0 parts by weight or less, and even more preferably 2.0 parts by weight or less. If the content of compound (B) is too low, the additive effect of compound (B) may not be fully obtained; if it is too high, the manufacturing cost may increase.
[0107] The resin composition for foaming molding disclosed herein may contain a foaming nucleating agent other than compound (B). As a foaming nucleating agent other than compound (B), there are no particular limitations as long as the above conditions are not met. Examples include boron nitride, sodium 2,2'-methylene bis(4,6-di-tert-butylphenyl) phosphate, barium fluorooctane sulfonate, barium bisphenol phosphate diester, N,N'-dicyclohexyl-2,6-naphthalenedicarboxylate, sodium phenylphosphonate, 2,6-naphthalenedicarboxylic acid, 1,3:2,4-bis-O-(4-methylbenzyl)-D-sorbitol, N,N'-di(octadecyl)isophthalamide, sodium benzoate, sodium bis(4-nitrophenyl) phosphate, triaminobenzene derivatives, 1,3,5-tris(2,2-dimethylpropionylamino)benzene, Pigment Red 254, talc, sodium binaphthalene phosphate, barium tert-butyl-binaphthalene phosphate, rosin metal salts, condensed phosphate esters, etc. In addition, sulfonic acid, sulfonates, phosphonic acid, phosphonates, zeolites, ADCA (azodicarbonamide), DPT (N,N'-dinitropentamethylenetetramine), OBSH (4,4'-oxobis(benzenesulfonylhydrazine)), etc. can be used. One or more of them can be used.
[0108] The resin composition for foaming molding disclosed herein may further contain inorganic salts containing polyatomic anions without impairing the effects of the present disclosure.
[0109] Examples of inorganic salts containing polyatomic anions include the substances disclosed in U.S. Patent No. 4,764,538.
[0110] The resin compositions for foaming molding disclosed herein may include conventionally known filler materials to a extent that does not impair the effects of the present disclosure.
[0111] Examples of filler materials include graphite, carbon fiber, coke, silica, zinc oxide, magnesium oxide, magnesium sulfate, tin oxide, antimony oxide, calcium carbonate, magnesium carbonate, magnesium hydroxide, glass, talc, mica, aluminum nitride, calcium phosphate, sericite, diatomaceous earth, silicon nitride, fine silica, fumed silica, alumina, zirconium oxide, quartz powder, kaolin, bentonite, and titanium dioxide. One or more of these materials can be used. The shape of the filler material is not particularly limited and can include fibrous, needle-like, columnar, whisker-like, plate-like, layered, scaly, hollow spherical, porous, short fiber-like, powder-like, granular, and bead-like forms. It should be noted that this filler material differs from boron nitride and other similar materials mentioned in foaming nucleating agents.
[0112] The resin composition for foaming molding disclosed herein may further contain other components such as additives. Examples of other components include fillers such as glass fibers, glass powder, asbestos fibers, cellulose fibers, and carbon fibers, as well as reinforcing agents, stabilizers, lubricants, pigments, flame retardants, and other additives.
[0113] If the resin contains a large amount of fluorine-based low-molecular-weight compounds, the molten resin during molding will be plasticized, sometimes resulting in more sparks. Therefore, the resin composition for foam molding disclosed herein is preferably substantially free of fluorine-based low-molecular-weight compounds.
[0114] It should be noted that, in essence, "free of fluorine-based low molecular weight compounds" means that the content of fluorine-based low molecular weight compounds is less than 10 ppm by mass.
[0115] There are no particular limitations on what constitutes a low-molecular-weight fluorine compound; for example, fluorine compounds with a molecular weight of less than 1000 can be cited. Specifically, perfluoroalkyl acids and perfluorosulfonic acids can be cited, and more specifically, C8F... 17 COOH and its salts, C7F 15 COOH and its salts, C6F 13 COOH and its salts, C8F 17 SO3H and its salts, C6F 13 SO3H and its salts, C4F9SO3H and its salts, C8F 17 CH2CH2-SO3H and its salts, C6F 13 CH2CH2-SO3H and its salts, C8F 17 CH2CH2OH, C6F 13 CH2CH2OH, etc., and more specifically, {F(CF2)6CH2CH2SO3}2Ba can be cited as an example.
[0116] The content of low molecular weight fluorine compounds can be analyzed using the following methods: The sample was pulverized by cryogenic grinding, and the resulting powder was dispersed in methanol. Extraction was then performed by ultrasonic treatment at 60°C for 2 hours. The extract was quantified using liquid chromatography-mass spectrometry (LC-MS / MS), and the obtained value was taken as the content.
[0117] The melt flow rate (MFR) of the resin composition for foaming molding disclosed herein is preferably 1 to 100 g / 10 min. More preferably, it is 5 to 70 g / 10 min, even more preferably 10 to 60 g / 10 min, and from the viewpoint of suppressing spark generation and increasing foaming rate, it is even more preferably 15 to 50 g / 10 min, even more preferably 20 to 45 g / 10 min, and particularly preferably 30 to 45 g / 10 min.
[0118] The above MFR is a value determined according to ASTM D-1238, using a die with a diameter of 2.1 mm and a length of 8 mm, under a load of 5 kg and a temperature of 372 °C.
[0119] To reduce signal loss in communication cables, the dielectric constant of the resin composition for foaming molding disclosed herein is preferably 3.0 or less, more preferably 2.5 or less, even more preferably 2.3 or less, and most preferably 2.1 or less. A lower limit of 1.0 or more is preferred. Similarly, the dielectric loss tangent is preferably 0.01 or less, more preferably 0.002 or less, even more preferably 0.001 or less, and most preferably 0.0005 or less. A lower limit of 0.0001 or more is preferred.
[0120] The dielectric constant and dielectric loss tangent of the resin composition for foaming molding disclosed herein were determined using the resin composition prior to foaming molding via a cavity resonator method at a frequency of 6 GHz.
[0121] The resin composition for foaming molding disclosed herein is suitable for use as a foaming composition, and in particular, is suitable for use as a wire coating composition for forming a coating layer for wires.
[0122] The method for manufacturing a foamed molded article disclosed herein includes a step of foaming and molding (preferably intermittent foaming and molding) the resin composition for foaming and molding disclosed herein.
[0123] In addition, the foamed molded articles of this disclosure are formed using the foamed molding resin composition of this disclosure.
[0124] Until now, in the intermittent foaming molding of fluororesins that require high-temperature molding, foaming nucleating agents capable of forming microbubbles are not common. The resin composition for foaming molding disclosed herein is also capable of forming microbubbles in the intermittent foaming molding of fluororesins.
[0125] There are no particular limitations on the method for foaming the resin composition for foaming molding disclosed herein. Conventionally known methods can be used, such as: feeding the resin composition for foaming molding disclosed herein into a screw extruder designed for foaming operation and using a continuous gas extrusion method; or, feeding the pre-formed resin composition for foaming molding disclosed herein into a pressure vessel, heating it to a predetermined temperature above the melting point, fully impregnating it with gas, and then rapidly depressurizing it by pressure release, etc.
[0126] The gas used in gas extrusion and batch foaming methods can be, for example, dichlorofluoromethane, nitrogen, carbon dioxide, or a mixture of the above gases. It can be introduced as a pressurized gas into the molten resin inside the extruder or into a pressure vessel, or it can be generated by mixing a chemical foaming agent into the molten resin or a pre-formed foaming molding resin composition. The introduced gas dissolves in the molten resin inside the extruder and in the resin inside the pressure vessel.
[0127] Gases dissolved in the resin are released from the molten material due to a sudden decrease in pressure as the molten material exits the extrusion die or a rapid decompression caused by the release of pressure from the pressure vessel. The extruded material is then cooled and cured by methods such as introducing it into water. In the case of intermittent foaming, the resin is also cooled and cured by cooling the pressure vessel.
[0128] The foamed body disclosed herein has a low dielectric constant, exhibits stable capacitance, and is lightweight. Therefore, as a coating material described later, it can achieve a shape with stable dimensions such as wire diameter and thickness, and further, as an insulating layer, it can achieve a shape with stable dimensions such as thickness.
[0129] The total volume of air bubbles in the foamed molded article disclosed herein can be appropriately adjusted, for example, according to the application, by adjusting the amount of gas inserted in the extruder or by selecting the type of dissolved gas.
[0130] The foamed molded body disclosed herein is obtained in the form of a molded body shaped according to its intended use when extruded from the aforementioned extruder. As for the aforementioned molding method, there is no particular limitation as long as it involves heating and melting molding, for example, extrusion foaming molding, injection foaming molding, die foaming molding, intermittent foaming molding, etc.
[0131] The shape of the foamed molded body disclosed herein is not particularly limited, and it can be made into various shapes such as coating materials for foamed wires; filaments such as wires; sheets; films; rods; tubes, etc. The aforementioned foamed molded body can be used, for example, as lightweight structural materials such as electrical insulation materials; heat insulation materials; sound insulation materials; suspending materials; and cushioning materials such as cushioning pads. Furthermore, the aforementioned foamed molded body is particularly suitable for use as a coating material for foamed wires.
[0132] The resulting foamed molded article is preferably a foamed molded article containing a melt-cured body of the foamed molding resin composition disclosed herein and bubbles, wherein the bubbles are uniformly distributed in the melt-cured body. The bubble size is not limited, but is preferably 60 μm or less, more preferably 30 μm or less. Furthermore, the bubble size is preferably 0.1 μm or more.
[0133] The air bubbles in the foamed molded article disclosed herein can be continuous air bubbles or independent air bubbles, preferably independent air bubbles. By using independent air bubbles, the following advantages are available: strong resistance to external pressure, excellent rigidity, impact absorption, and processability; furthermore, moisture and other substances will not penetrate the interior.
[0134] In addition to the heating and melting process mentioned above, independent bubbles can also be formed using previously known methods.
[0135] The foamed molded body disclosed herein is in a foamed state that is conducive to a low dielectric constant, and therefore can be used as an associated insulator for, for example, wire insulation layers, semiconductor packaging substrate insulation layers, transformer insulation layers, circuit board insulation layers, motor insulation layers, reactor insulation layers, transistor insulation layers, printed circuit board insulation layers, semiconductor device insulation layers, electronic component insulation layers, etc., and is particularly suitable for use as wire insulation layers (coating layers).
[0136] The implementation methods have been described above. However, it should be understood that various changes can be made to the methods and specific circumstances without departing from the spirit and scope of the claims.
[0137] Example
[0138] The present disclosure will now be described in more detail by way of examples, but the present disclosure is not limited to these examples.
[0139] The various characteristics described in this specification were measured using the following methods.
[0140] (Determination of unstable terminal base)
[0141] The granules were rolled using a hydraulic press to produce a membrane with a thickness of approximately 0.3 mm. The membrane was then analyzed using an FT-IR Spectrometer 1760X (manufactured by Perkin-Elmer).
[0142] Obtain the differential spectrum with the standard sample (the sample has been fully fluorinated until no substantial difference is found in the spectrum), read the absorbance of each peak, and calculate the absorbance relative to 1×10 using the following formula. 6 The number of unstable terminal groups of a carbon atom.
[0143] Compared to 1×10 6 The number of unstable terminal groups equal to the number of carbon atoms = (I×K) / t
[0144] (I: absorbance, K: correction factor, t: film thickness (unit: mm))
[0145] The correction coefficients (K) for each unstable terminal basis are as follows.
[0146] -COF(1884cm -1 )...405
[0147] -COOH(1813cm -1 1775cm -1 )...455
[0148] -COOCH3(1795cm -1 )...355
[0149] -CONH2(3438cm -1 )...480
[0150] -CH2OH(3648cm -1 )...2325
[0151] (Determination of -CF2H terminal group)
[0152] The measurement was performed using an AC300 nuclear magnetic resonance apparatus (manufactured by Bruker-Biospin), with the measurement temperature set to the melting point of fluoropolymer (A) +20°C. 19 F-NMR determination, obtained by integrating the peaks originating from the presence of the -CF2H group with the integrals of other peaks.
[0153] (SSG)
[0154] The determination was performed according to ASTM D4895-89, based on the water displacement method.
[0155] (Melting point)
[0156] Using a DSC (SEIKO Electronics RDC220), the temperature corresponding to the peak measured at a heating rate of 10°C / min is taken as the melting point.
[0157] (Thermal decomposition temperature)
[0158] The 1% weight reduction temperature when heated in air at 10°C / min was determined by TG.
[0159] (MFR)
[0160] MFR is the value measured according to ASTM D-1238 using a KAYENESS Melt Indexer Series 4000 (manufactured by Yasuda Seiki Co., Ltd.) with a die head of 2.1 mm in diameter and 8 mm in length, at 372°C and a 5 kg load.
[0161] The examples and comparative examples are implemented using the following methods.
[0162] (Preparation of FEP pellets)
[0163] Fluorinated FEP pellets were prepared using the same method as in Example 2 of Japanese Patent Application Publication No. 2011-514407. The resulting pellets (TFE / HFP / PPVE copolymer) had a TFE / HFP / PPVE ratio of 87.8 / 11.2 / 1.0 (mass ratio), a melting point of 255°C, an MFR of 23 g / 10 min, and a total number of unstable end groups and -CF2H end groups relative to 1 × 10⁻⁶. 6 There are 3 carbon atoms in each carbon atom.
[0164] (Preparation of granules for intermittent foaming test (Step 1))
[0165] For FEP granules (MFR: 38 g / 10 min), additives were mixed to achieve the target concentration, and the mixture was kneaded at 300°C for 10 minutes using a torque rheometer (LABO PLASTOMILL) to prepare a compound. The recycled mixture was cut and extruded using an MFR measuring device at 300°C and a 5 kg load. The extruded filaments were then cut into 2–3 mm pieces to prepare granules.
[0166] The cross-section of the prepared granules was photographed at 150x magnification using a laser microscope (KEYENCE VK-X1000 shape analysis laser microscope). The distance between the centers of gravity of the nucleating agent particles, particle density, and particle size were calculated through image processing. The distance between the centers of gravity and particle size are the average values of 100 particles.
[0167] (Intermittent foaming test (process 2))
[0168] The internal volume after being fully preheated in a 270℃ electric furnace is approximately 11 cm³. 3 0.4g of granules encased in aluminum foil was sealed into a pressure vessel and returned to the electric furnace. A maximum of three samples were sealed simultaneously in one test. The pressure was increased to 3MPa with nitrogen and maintained for 60 minutes, then rapidly reduced to atmospheric pressure within one second to foam the resin. The resulting foamed molded body maintained the granule shape. Furthermore, it was not an unfoamed state (only exhibiting cracks).
[0169] SEM images of the cross-section of the foamed molded article were taken, and the number of bubbles per unit area was calculated through image processing. The bubble number per unit area was defined as the multiple of the number of bubbles produced when the same treatment was performed on resin without additives. In addition, the average area of each bubble was calculated, and the average bubble area was defined as the multiple of the bubble area produced when the same treatment was performed on resin without additives.
[0170] (Crystal size)
[0171] X-ray diffraction equipment: Smart Lab, manufactured by Rigaku Corporation; measurement and analysis software: Smart LabStudioII. The X-ray source was CuKα with a wavelength of 1.54 Å, and the diffraction angle (2θ) was set to 5°–90°. The crystallite size was calculated using the Scherrer formula from the maximum half-width of the obtained diffraction peaks.
[0172] D=K×λ / (β×cosθ)…Scherrer’s formula
[0173] D: Crystalline size (Å)
[0174] K: Scherrer constant
[0175] λ: X-ray wavelength (Å)
[0176] β: Half-width of the diffraction peak (rad)
[0177] θ: 1 / 2 (rad) of the diffraction angle
[0178] Scherrer constant (K) = 0.94, X-ray wavelength (λ) = 1.5418. The case where the obtained diffraction spectrum does not contain diffraction peaks originating from the crystal structure is considered as the case without a crystal structure, and the crystallite size is set to peakless.
[0179] (Volatileness test)
[0180] The amount of mass reduction of the sample (additive) when held at 330℃ in an electric furnace for 1 hour is determined, and the amount of volatilization is calculated by dividing the amount of mass reduction by the mass before holding by 100.
[0181] (Content of fluorine-based low-molecular-weight compounds)
[0182] The sample was pulverized by cryogenic grinding, and the resulting powder was dispersed in methanol. Extraction was then performed by ultrasonic treatment at 60°C for 2 hours. The extract was quantified using liquid chromatography-mass spectrometry (LC-MS / MS), and the obtained value was taken as the content.
[0183] (Dielectric constant, dielectric loss tangent)
[0184] For the intermittent foaming test granules (resin composition before foaming) for the target additive concentration, the determination was performed using the cavity resonator method at a frequency of 6 GHz.
[0185] (State of compound (B) at molding temperature)
[0186] Using a polarizing microscope equipped with a heated stage, observe whether compound (B) exists in a solid state when the temperature is raised to a specified temperature.
[0187] Example 1
[0188] In step 1, granules containing 1 part by mass of copper phthalocyanine (manufactured by Tokyo Chemical Industry Co., Ltd., melting point: no peak detected below 350°C, thermal decomposition temperature: 388°C, crystallite size: 103 Å, volatility in volatility test: 0.4% by mass) were prepared relative to 100 parts by mass of FEP granules. In step 2, a foamed molded body was obtained. The distance between the centers of gravity of the additive particles dispersed in the granules prepared in step 1 was 1.6 μm. The bubble number index per unit area in the intermittent foaming test of step 2 was 21, which is good.
[0189] Furthermore, no fluorine-based low-molecular-weight compounds were detected in the granules used or the foamed molded articles produced. No fluorine-based low-molecular-weight compounds were also detected in the subsequent examples and comparative examples.
[0190] In addition, copper phthalocyanine does not decompose, dissolve in FEP, or melt at the molding temperature during foaming.
[0191] Furthermore, SEM images of the cross-section of the foamed molded body confirmed the formation of individual air bubbles. Individual air bubbles were also formed in subsequent embodiments and comparative examples.
[0192] Example 2
[0193] As an additive, hollow white sand spheres (SSW-40 manufactured by Zanwers Co., Ltd., main components: silica and alumina, melting point: no peak detected below 350°C, thermal decomposition temperature: above 600°C, crystallite size: 672 Å, volatility in volatility test: 0.0%) were used. Otherwise, a foamed molded body was obtained using the same method as in Example 1. The distance between the centers of gravity of the additive particles dispersed in the granules produced in step 1 was 2.9 μm. The bubble number index per unit area in the intermittent foaming test of step 2 was 13, which is good.
[0194] In addition, at the molding temperature during foaming, the white sand hollow spheres do not decompose, dissolve in FEP, or melt.
[0195] Example 3
[0196] As an additive, precipitated barium sulfate (P-30 manufactured by Takehara Chemical Industry Co., Ltd., melting point: no peak detected below 350°C, thermal decomposition temperature: above 600°C, crystallite size: 309 Å, volatility in volatility test: 0.0%) was used. Otherwise, the foamed molded body was obtained using the same method as in Example 1. The distance between the centers of gravity of the additive particles dispersed in the granules prepared in step 1 was 2.8 μm. The bubble number index per unit area in the intermittent foaming test of step 2 was 13, which is good.
[0197] In addition, at the molding temperature during foaming, precipitated barium sulfate does not decompose, dissolve in FEP, or melt.
[0198] Example 4
[0199] As an additive, perlite powder (W-6 manufactured by Takehara Chemical Industry Co., Ltd., main component: barium sulfate, melting point: no peak detected below 350°C, thermal decomposition temperature: above 600°C, crystallite size: 153 Å, volatility in volatility test: 0.0%) was used. Otherwise, a foamed molded body was obtained using the same method as in Example 1. The distance between the centers of gravity of the additive particles dispersed in the granules prepared in step 1 was 2.9 μm. The bubble count index per unit area in the intermittent foaming test of step 2 was 12, which is good.
[0200] In addition, perlite powder does not decompose, dissolve in FEP, or melt at the molding temperature during foaming.
[0201] Comparative Example 1
[0202] Boron nitride (MGP manufactured by Denka Corporation, crystallite size: 158 Å, volatility in volatility test: 0.0%) was used as an additive, and the foamed molded body was obtained by the same method as in Example 1. The distance between the centers of gravity of the additive particles dispersed in the granules produced in step 1 was 5.9 μm. The number of bubbles per unit area in the intermittent foaming test of step 2 was as low as 7.3.
[0203] Comparative Example 2
[0204] Sodium benzoate (manufactured by Fujifilm and Kojun Chemical Co., Ltd., crystallite size: 131 Å, volatility in volatility test: 0.0%) was used as an additive, and the foamed molded body was obtained by the same method as in Example 1. The distance between the centers of gravity of the additive particles dispersed in the granules prepared by step 1 was 6.2 μm. The number of bubbles per unit area in the intermittent foaming test was as low as 5.4.
[0205] Comparative Example 3
[0206] Pigment Red 254 (manufactured by Tokyo Chemical Industry Co., Ltd., crystallite size: 89 Å, volatility in volatility test: 0.4%) was used as an additive, and the foamed molded article was obtained by the same method as in Example 1. The distance between the centers of gravity of the additive particles dispersed in the granules produced in step 1 was 2.2 μm. The number of bubbles per unit area in the intermittent foaming test of step 2 was as low as 3.1.
[0207] Comparative Example 4
[0208] Talc (PAOG-2 manufactured by Tokyo Chemical Industry Co., Ltd., crystallite size: 37 Å, volatility in volatility test: 0.0%) was used as an additive, and the foamed molded body was obtained by the same method as in Example 1. The distance between the centers of gravity of the additive particles dispersed in the granules produced in step 1 was 5.1 μm. The number of bubbles per unit area in the intermittent foaming test of step 2 was as low as 4.6.
[0209] Comparative Example 5
[0210] As an additive, a rosin metal salt (Plafit H510H manufactured by Arakawa Chemical Industry Co., Ltd., no XRD peaks observed, volatility in the volatility test: 10.6% by mass) was used. Otherwise, the foamed molded body was obtained using the same method as in Example 1. The distance between the centers of gravity of the additive particles dispersed in the granules produced in step 1 was 4.2 μm. The bubble number index per unit area in the intermittent foaming test of step 2 was as low as 0.4.
[0211] Comparative Example 6
[0212] As an additive, a condensed phosphate ester (SR-3000 manufactured by Daihachi Chemical Industry Co., Ltd., no XRD peaks observed, volatility in the volatility test: 8.1% by mass) was used. Otherwise, the foamed molded body was obtained using the same method as in Example 1. The distance between the centers of gravity of the additive particles dispersed in the granules produced in step 1 was 4.1 μm. The bubble number index per unit area in the intermittent foaming test of step 2 was as low as 0.2.
[0213] Comparative Example 7
[0214] Without using any additives, the foamed molded body was obtained using the same method as in Example 1. The number of bubbles per unit area in the intermittent foaming test using the foamed molded body was set to 1.0, and the average bubble area index was set to 1.00.
[0215] [Table 1]
Claims
1. A resin composition for foaming molding, comprising a fluoropolymer (A) and a compound (B), wherein the compound (B) has a crystallite size greater than 100 Å as determined by X-ray diffraction and a volatility of less than 7.0% by mass at 330°C. The compound (B) is dispersed in the fluororesin (A) with a center-to-gravity distance of less than 5.0 μm.
2. The resin composition for foaming molding as described in claim 1, wherein, The fluororesin (A) is a fluororesin that can be melt-formed.
3. The resin composition for foaming molding as described in claim 1 or 2, wherein, The fluororesin (A) is selected from at least one of the groups consisting of tetrafluoroethylene / hexafluoropropylene copolymers and tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymers.
4. The resin composition for foaming molding according to any one of claims 1 to 3, wherein, The fluororesin (A) is a tetrafluoroethylene / hexafluoropropylene copolymer.
5. The resin composition for foaming molding according to any one of claims 1 to 4, wherein, The fluoropolymer (A) has undergone fluorination treatment.
6. The resin composition for foaming molding according to any one of claims 1 to 5, wherein, The content of the fluoropolymer (A) is 80% to 99.99% by mass.
7. The resin composition for foaming molding according to any one of claims 1 to 6, wherein, The content of the fluoropolymer (A) is 97% by mass or more and less than 99.85% by mass.
8. The resin composition for foaming molding according to any one of claims 1 to 7 is substantially free of fluorine-based low molecular weight compounds.
9. The resin composition for foaming molding according to any one of claims 1 to 8, wherein, The crystallite size of the compound (B) in X-ray diffraction is 200 Å to 1000 Å, and the volatilization at 330 °C is less than 1.0% by mass.
10. The resin composition for foaming molding according to any one of claims 1 to 9, wherein, The compound (B) is dispersed in the fluororesin (A) with a center-to-gravity distance of 0.5 μm to 2.0 μm.
11. The resin composition for foaming molding according to any one of claims 1 to 10, wherein, The compound (B) has a density of 15,000 particles / mm². 2 The above are dispersed in the fluororesin (A).
12. The resin composition for foaming molding according to any one of claims 1 to 11, wherein, The compound (B) is dispersed in the fluororesin (A) with a particle size of less than 4.0 μm.
13. The resin composition for foaming molding according to any one of claims 1 to 12, wherein, The thermal decomposition temperature of the compound (B) is above 270°C.
14. The resin composition for foaming molding according to any one of claims 1 to 13, wherein, The compound (B) comprises at least one selected from the group consisting of tetrapyrrole cyclic compounds, barium sulfate, silicon dioxide and aluminum oxide.
15. The resin composition for foaming molding according to any one of claims 1 to 14, wherein, The compound (B) contains copper phthalocyanine.
16. The resin composition for foaming molding according to any one of claims 1 to 15, wherein, The content of compound (B) is 0.1 to 20 parts by mass relative to 100 parts by mass of the fluororesin (A).
17. The resin composition for foaming molding according to any one of claims 1 to 16, wherein, The content of compound (B) is 0.5 to 2.0 parts by mass relative to 100 parts by mass of the fluoropolymer (A).
18. A foamed molded article formed using the foamed molding resin composition according to any one of claims 1 to 17.
19. A method for manufacturing a foamed molded article, comprising a step of foaming a resin composition for foaming molding according to any one of claims 1 to 17.
20. The method for manufacturing a foamed molded article as described in claim 19, wherein, The foaming process is an intermittent foaming process.
Citation Information
Patent Citations
Tetrafluoroethylene / hexafluoropropylene copolymer and method for producing the same, and electric wire
JP2011514407A
Foam
JP2015004057A
Foam nucleation system for fluoropolymers
US4764538A